Intrinsic Features of an Ideal Glass - 孙得彦 商城 刘智攀 龚新高 (Chinese physics letters, 2017)
In order to understand the long-standing problem of the nature of glass states, we perform intensive simulations on the thermodynamic properties and potential energy surface of an ideal glass. It is found that the atoms of an ideal glass manifest cooperative diffusion, and show clearly different behavior from the liquid state. By determining the potential energy surface, we demonstrate that the glass state has a fiat potential landscape, which is the critical intrinsic feature of ideal glasses. When this potential region is accessible through any thermal or kinetic process, the glass state can be formed and a glass transition will occur, regardless of any special structural character. With this picture, the glass transition can be interpreted by the emergence of conlgurational entropies, as a consequence of flat potential landscapes.